Positive and Negative Impact of Gadget Use in Teenagers' Lives - Manik, Novida Dwici Yuanri; Sutrisno, Sutrisno (Scriptura Indonesia, 2024)
Technological development is something that cannot be avoided in this modern era. This is because all human needs can be obtained by using this technology. Humans must be able to develop as technology continues to advance every day. However, behind the benefits of technology that can facilitate the fulfillment of human needs, this technology can also hinder human progress. It depends on how humans use and utilize this technology. Today's teenagers are also very dependent on gadgets, both for social needs, education and daily needs. This article aims to see how the positive and negative impacts of gadget use are in the lives of teenagers, so that readers can also know how to maximize the use of gadgets for positive things.